Ilmu Kalam “Terapan”: Sebuah Reorientasi menuju Kajian Ilmu Kalam yang Implementatif - M. Amin Nurdin; Dadi Darmadi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2008)
This text is an effort to make Ilmu Kalam (Islamic theology) an applied science. Now is the right time to revive the study of Ilmu Kalam by reorienting its methods and core topics towards more practical applications, so that this discipline once again becomes a rich, intelligent, and inspiring intellectual heritage of Islam for solving the problems of humanity. This reorientation effort is not at all intended to dismantle a scientific structure that is already so solid; rather, it is meant to enrich the great and brilliant discipline of Ilmu Kalam. However, this greatness and brilliance will be in vain if not accompanied by efforts to revitalize it in accordance with its current significance.